Transformation metabolites of phthalate esters (PAEs) inhibited rice growth through jasmonic acid signaling pathway - Sun, Yingying; Chen, Jie; Wang, Wei; Zhu, Lizhong (Environment international, 2025)
[Display omitted] •Pest defense and growth indication were induced in rice by dibutyl phthalate (DBP).•DBP metabolites MBP activated the jasmonic acid (JA) signaling pathway as JA analogue.•MBP conjugated with isoleucine and then bound to the COI1/JAZ co-receptor complex.•Aliphatic chain length of PAEs were negatively contributed to the JA-related outcomes. Phthalate esters (PAEs) were ubiquitous in agricultural soils and could be metabolized after being absorbed by crops, posing significant implications for crop yield and quality. We hypothesize that monophthalates (mPAEs), the hydrolyzed products of PAEs, might mimic phytohormone jasmonic acid (JA) to activate the JA signaling pathway, therefore enhancing the defense towards pests and inhibiting the rice plant growth. Taking dibutyl phthalate (DBP) as a representative PAE, our study discovered that DBP exposure significantly induced JA-related outcomes including decreased larval weight (9.58–18.8%), and rice biomass (11.7–34.2%). Under the conditions where the JA content remained unchanged, monobutyl phthalate (MBP), the hydrolyzed product of DBP, triggered the JA signaling pathway, evidenced by significantly upregulated genes encoding coronatine insensitive 1 (COI1) (1.56–1.73 fold), jasmonate ZIM-domain (JAZ) (4.33–7.71 fold), MYC2 transcription factor (2.07–2.87 fold), and promoted phytoalexins production in downstream signaling. MBP conjugated with isoleucine, and the conjugate subsequently mimicked a JA bioactivator (JA-isoleucine conjugate) to occupy the binding site of COI1-JAZ co-receptor protein, thereby initiating the JA signaling pathway. These JA-related outcomes and mechanism were consistently evidenced in rice exposed to other four typical PAEs, and the aliphatic chain length of selected PAEs indicated a negative contribution to these observations. In this study, we discovered a unconventional mechanism through which the transformation metabolites of PAEs elicit pest defense while simultaneously inhibiting rice growth, providing insights into the risk assessment of PAEs on crop yields and quality.